STIGMATISATION OF HIV-POSITIVE MEMBERS OF THE WORKFORCE - Nowell, JH; van der Merwe, RP (Social Work/Maatskaplike Werk, 2003)
The rate at which the Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) is spreading throughout the world, especially Africa, is alarming. Although Africa contains only about 12% of the world’s population, it contains over 70% of HIV-infected individuals. It is estimated that over 10% of the South African population is HIV positive (Addison, 2001). This pandemic is a threat to the economy, individual workers and society in general (House, Eicken & Gray, 1995). Social implications of HIV/AIDS include fear, prejudice, discrimination, hysteria, stigmatisation and other irrational responses from members of society (Herek & Glunt, 1988; House et al., 1995). For the purpose of this study, "stigmatisation" refers to the irrational responses (including fear, attitudes and prejudicial behaviour) by co-workers and/or superiors within the work environment towards HIV positive individuals.